THE EFFECT OF AUTHORITATIVE PARENTING ON SELF DIRECTION SKILLS IN PRIMARY SCHOOL STUDENTS - Ika Dwi Lestari (Jurnal Cakrawala Pendas, 2023)
The efforts to develop self direction skills are not only driven by learning program implemented by school. This study aims to determine the effect of authoritative parenting on self direction skills in primary school students. This study used the ex post facto method with a correlation research design. The sample technique is purposive sampling through observation, interviews and questionnaires. Therefore, the importance of the role of parents through the application of proper parenting, so that students can develop self direction skills. The total of samples in this study were 50 parents and 25 children. The selection of this sample is based on the results of observations and interviews that refer to parents who apply authoritative parenting and children who are given this treatment. The data analysis techniques use validity test on parenting experts, reliability test, normaility test, linearity test, correlation test, regression test and termination test. The results of the study obtained a Sig value of 0,000 < 0,05 and the coefficient of determination test obtained a value of 0,900. This is consistent with the purpose of this study, that there is a positive influence between authoritative parenting on self direction skills by 90%. Upaya pengembangan keterampilan self direction tidak hanya didorong oleh program pembelajaran yang dilaksanakan oleh sekolah. Oleh karena itu, pentingnya peran orang tua melalui penerapan pola asuh yang tepat, agar peserta didik dapat mengembangkan keterampilan self direction. Penelitian ini bertujuan untuk mengetahui pengaruh pola asuh authoritative parenting terhadap keterampilan self direction pada siswa sekolah dasar. Penelitian ini menggunakan metode ex post facto dengan desain penelitian korelasi. Teknik pengambilan sampel purpossive sampling melalui observasi, wawancara dan angket. Jumlah sampel dalam penelitian ini yaitu 50 orang tua dan 25 anak. Pemilihan sampel ini didasarkan pada hasil observasi dan wawancara yang merujuk pada orang tua yang menerapkan pola asuh authoritative parenting serta anak yang di beri perlakuan tersebut. Teknik analisa data menggunakan uji validitas kepada ahli parenting, uji reliabilitas, uji normalitas, uji linieritas, uji korelasi, uji regresi dan uji determinasi. Hasil penelitian memperoleh nilai Sig 0,000 < 0,05 dan uji koefisien determinasi memperoleh nilai 0,900. Hal tersebut sesuai dengan tujuan penelitian bahwa terdapat pengaruh yang positif antara pola asuh authoritative parenting terhadap keterampilan self direction sebesar 90%.